Whole-cell biocatalysis using cytochrome P450 monooxygenases for biotransformation of sustainable bioresources (fatty acids, fatty alkanes, and aromatic amino acids) - Park, Hyun A.; Park, Gyuyeon; Jeon, Wooyoung; Ahn, Jung Oh; Yang, Yung Hun; Choi, Kwon Young (Biotechnology Advances, 2020)
Cytochrome P450s (CYPs) are heme-thiolated enzymes that catalyze the oxidation of C[sbnd]H bonds in a regio and stereoselective manner. Activation of the non-activated carbon atom can be further enhanced by multistep chemo-enzymatic reactions; moreover, several useful chemicals can be synthesized to provide alternative organic synthesis routes. Given their versatile functionality, CYPs show promise in a number of biotechnological fields. Recently, various CYPs, along with their sequences and functionalities, have been identified owing to rapid developments in sequencing technology and molecular biotechnology. In addition to these discoveries, attempts have been made to utilize CYPs to industrially produce biochemicals from available and sustainable bioresources such as oil, amino acids, carbohydrates, and lignin. Here, these accomplishments, particularly those involving the use of CYP enzymes as whole-cell biocatalysts for bioresource biotransformation, will be reviewed. Further, recently developed biotransformation pathways that result in gram-scale yields of fatty acids and fatty alkanes as well as aromatic amino acids, which depend on the hosts used for CYP expression, and the nature of the multistep reactions will be discussed. These pathways are similar regardless of whether the hosts are CYP-producing or non-CYP-producing; the limitations of these methods and the ways to overcome them are reviewed here.
Keywords: Aromatic amino acid; Biotransformation pathways; Cytochrome P450 monooxygenases; Molecular biotechnology; Monooxygenases; Oxyfunctionalization; Whole cell biocatalysts; Whole-cell biocatalysis; Alkanes; Amino Acids, Aromatic; Biocatalysis; Biotransformation; Cytochrome P-450 Enzyme System; Fatty Acids; Aromatic amino acids; Cytochrome P450 monooxygenase; Fatty acids; Fatty alkanes; Oxyfunctionalization; Whole-cell biocatalyst